Investigations of Archaeological Glass Bracelets and Perfume Bottles Excavated in Ancient Ainos (Enez) by Multiple Analytical Techniques - Özel, Ayşen E.; Kecel Gündüz, Serda; Başaran, Sait; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Springer, 233 Spring St, New York, Ny 10013 USA, 2018)
Fragments of two perfume bottles belonging to the Hellenistic and Roman periods, and five bracelets belonging to the Roman, Byzantine, and Ottoman periods, excavated in the archaeological site of Enez during the excavations in 2000, have been investigated. The samples were analyzed using micro-Raman, FTIR, and energy dispersive X-ray fluorescence techniques, in order to study the ancient technology of glass production and to determine chemical compositions of the basic components and coloring elements of the glassware. All the investigated glasses can be characterized as low-magnesia-soda-lime silicate glasses, whose colors are induced by metal ions. The melting points of the investigated glasses are estimated to be quite close to each other and around 1000A degrees C.
Keywords: energy dispersive X-ray fluorescence; historical glasses; IR and Raman spectroscopy; Site Raman Identification; Stained Glasses; Silica Glasses; Polymerization; Spectra